Pengaruh Formulasi Bahan Baku dan CMC (Carboxy Methyl Cellulose) Terhadap Mutu dan Penerimaan Konsumen Susu Nabati - Dian Hasni; Irfan Irfan; Rina Saputri (Jurnal Teknologi dan Industri Pertanian Indonesia, 2021)
Nowadays, consumers tend to search for additional source of protein and energy for their dietary consumption, for instance from legumes and nuts. This trend is getting more common since the increase case of lactose intolerance. This study aims to study the effect of the formulation of materials consisting of a mixture of two or three types of nuts and the CMC (Carboxy Methyl Cellulose)  on the quality characteristics of plant milk and consumer preferences towards the produced plant milk. The method used in this study was a factorial completely randomized design (FCRD). This study were used combination of two or three types of beans, namely soybeans (KK), peanuts (KT), green beans (KH). The first factor was formulation of raw materials (K1 = 50% KK: 50% KT: 0% KH, K2 = 50 % KK: 0% KT: 50% KH, K3 = 0% KK: 50% KT: 50% KH, and K4 = 33.3% KK: 33.3% KT: 33.3% KH). In addition, CMC was used as a stabilizer by treating different concentrations of CMC (C1 = 0.20% and C2 = 0.40%). Anova continued with DMRT0.05 determined that plant milk with the best treatment is K1C2 with the formulation of 50% peanut: 50% soybean and the addition of 0.4% CMC. The KIC2 treatment had values: protein content 3.87%, fat content 14.74%, pH 6.62, total dissolved solids 11.47oBrix. For consumer acceptance with RATA (Rate All That Apply) method, researchers found out that K1C2 has milky white color (89% of respondents), peanut aroma flavour (78% respondents), sweet (48%) and savory (37%) taste, thick and homogenous texture (44% respondents) with overall hedonic liking 3.11 or neutral. Protein content, fat content, and pH of vegetable milk meet the quality requirements of soy milk based on SNI No. 01-3830-1995.